Translation and validation of student attitude assessment instrument towards science learning - Erlin Eveline; Hiba Dertyana Siregar; Rindah Permatasari (Privietlab, 2025)
Adapting research instruments presents challenges, as incorrect adaptation can affect the validity and reliability of the measurement. The study aims to adapt an instrument that is available in different languages. The adapted instrument is designed to assess students’ attitudes towards science learning in the classroom. The use of adapted research instruments with other cultures or across cultures affects the results obtained. The method used is back-end translation, followed by a pilot test of the translated instrument with respondents. Back-end translation was performed by translating the original instrument from English to Indonesian. The pilot test was conducted on 85 high school students. The instrument is considered equivalent if there are similarities or if the results of the validity and reliability tests are not significantly different from those of the original instrument. The results of the analysis of the adapted instrument show that it is valid and reliable. Compared with the original instrument, the instrument yielded results similar to those of the original version. These results suggest that the instrument is both equivalent and suitable for assessing students' attitudes towards science learning. The instrument adaptation method can be considered successful.